Neuartige Drehgelenke für reibungsarme Mechanismen : Auslegungskriterien und Berechnungsmethoden - Kern, Dominik (Schriftenreihe des Instituts für Technische Mechanik, Karlsruher Institut für Technologie, 2013)
In many branches of technology is a need for mechanisms with minimum friction and minimum bearing play. Such mechanisms are neither feasible with conventional hinges nor with hinges from the micro- and nanopositioning. This thesis proposes novel hinges in order to bridge the gap between the precision of micropositioning and the workspace of applications in manufacturing. The proposed implementations are flexure hinges for large displacements and dry slide bearings with friction reduction.